Unlocking the Potential in a Gamification-Based MOOC: Assessing Autonomous Learning and Self-Directed Learning Behaviors - Slamet, Joko; Basthomi, Yazid; Ivone, Francisca Maria; Eliyanah, Evi (Teaching and Learning Inquiry, 2024)
Massive open online courses (MOOCs) have significantly advanced online education. Yet, MOOC instructors still grapple with the ongoing challenge of low learner engagement while striving to foster autonomous and self-directed learning (SDL). Integrating gamification into these courses could be a promising solution. However, the extent to which gamification shapes autonomous and SDL behaviors within MOOCs remains underexplored. This mixed-methods sequential explanatory study investigates the interplay between MOOC, gamification, autonomous learning, and SDL behaviors to harness the potential of online education. We address this research void by delving into the intricate relationship between gamification and learners’ engagement in autonomous learning and SDL behaviors. Drawing upon self-determination theory (SDT) as a theoretical framework, we scrutinize how gamified MOOCs influence intrinsic motivation and SDL behaviors. Our study utilizes questionnaires and structured interviews to comprehensively examine the users’ experiences within a gamified MOOC. The findings suggest that thoughtfully integrated gamification elements not only enhance learner engagement but also stimulate autonomous learning and SDL behaviors. However, it is crucial to approach the integration of gamification thoughtfully, ensuring a balance that promotes intrinsic motivation without undue reliance on extrinsic motivators. These findings hold significant implications for educators, course designers, and policymakers leveraging gamification to enrich online learning experiences and cultivate self-directed educational pathways. They offer valuable insights for educators, course designers, and policymakers aiming to leverage gamification for enriching online learning experiences and nurturing self-directed educational pathways in MOOCs. Read the corresponding ISSOTL blog post here.